Design of a tamarind (Tamarindus indica L.) leaf jelly processing plant - Almaquer, Francis Eric P. (Miagao, Iloilo, Philippines University of the Philippines School of Science and Technology, 2013)
A plant was design for the productin of jelly from tamarind leaves.
Sotech thesis.
Keywords: Tamarind